Probing the Action of Permeation Enhancers Sodium Cholate and N-dodecyl-β-D-maltoside in a Porcine Jejunal Mucosal Explant System - E. Michael Danielsen; Gert H. Hansen (MDPI AG, 2018)
The small intestinal epithelium constitutes a major permeability barrier for the oral administration of therapeutic drugs with poor bioavailability, and permeation enhancers (PEs) are required to increase the paracellular and/or transcellular uptake of such drugs. Many PEs act as surfactants by perturbing cell membrane integrity and causing permeabilization by leakage or endocytosis. The aim of the present work was to study the action of sodium cholate (NaC) and N-dodecyl-β-D-maltoside (DDM), using a small intestinal mucosal explant system. At 2 mM, both NaC and DDM caused leakage into the enterocyte cytosol of the fluorescent probe Lucifer Yellow, but they also blocked the constitutive endocytotic pathway from the brush border. In addition, an increased paracellular passage of 3-kDa Texas Red Dextran into the lamina propria was observed. By electron microscopy, both PEs disrupted the hexagonal organization of microvilli of the brush border and led to the apical extrusion of vesicle-like and amorphous cell debris to the lumen. In conclusion, NaC and DDM acted in a multimodal way to increase the permeability of the jejunal epithelium both by paracellular and transcellular mechanisms. However, endocytosis, commonly thought to be an uptake mechanism that may be stimulated by PEs, was not involved in the transcellular process.